The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1806-9061-2017-0506
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Co-infection of Avian Leukosis Virus (subgroups A-E) and Reticuloendotheliosis Virus in Green Peafowls (Pavo muticus)

Abstract: Most of the neoplastic diseases affecting poultry have a viral etiology, such as Marek's disease, avian leukosis/sarcoma and reticuloendotheliosis. In the present paper, histopathology and molecular methods were performed, in addition of necropsy and gross morphology evaluation, for the differential diagnosis of these diseases in two green peafowls (Pavo muticus). The affected birds showed nonspecific signs, such as depression, anorexia, and diarrhea. At necropsy, diffuse enlargement by several times the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This finding is similar to the findings of Vascellari et al (2009) [15], who reported similar results in dogs and cats and partly agrees with the findings of Witter et al (1973) [25], who reported that older birds were fully susceptible to infection with Marek's disease virus and were only slightly resistant to the development of microscopic lesions. This is also similar to the findings of Sani et al (2017) [26] for chicken and Khordadmehr et al (2017) [27], in Pea fowls. Therefore, age, breed and sex are major risk factors for neoplasm development as similarly observed in the reports of Garcia et al (2019) [24].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to the findings of Vascellari et al (2009) [15], who reported similar results in dogs and cats and partly agrees with the findings of Witter et al (1973) [25], who reported that older birds were fully susceptible to infection with Marek's disease virus and were only slightly resistant to the development of microscopic lesions. This is also similar to the findings of Sani et al (2017) [26] for chicken and Khordadmehr et al (2017) [27], in Pea fowls. Therefore, age, breed and sex are major risk factors for neoplasm development as similarly observed in the reports of Garcia et al (2019) [24].…”
Section: Discussionsupporting
confidence: 90%
“…REV was also integrated into another DNA virus, Marek's disease as demonstrated by Davidson and Silva, (2008). Many studies have reported that coinfection of REV with Marek's disease and Avian leukosis complex in poultry (Khordadmehr et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Natural infection by ALV-A through E has been reported in other birds, including two green peafowl (Pavo muticus) with neoplasia [146] and in wild ostriches from a farm in Zimbabwe, which tested positive for antibodies and at least one case had clinical illness [147].…”
Section: Alv Prevalence In Non-chicken Speciesmentioning
confidence: 94%